2019
DOI: 10.1093/carcin/bgz088
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental estrogen and caloric restriction reduce obesity-induced periprostatic white adipose inflammation in mice

Abstract: Abstract Obesity is associated with an increased incidence of high-grade prostate cancer (PC) and worse prognosis for PC patients. Recently, we showed in men that obesity-related periprostatic white adipose tissue (WAT) inflammation, characterized by macrophages surrounding dead or dying adipocytes forming crown-like structures, was associated with high-grade PC. Possibly, interventions that suppress periprostatic WAT inflammation will improve outcomes for men wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
(64 reference statements)
1
11
0
Order By: Relevance
“…As a major female hormone, estrogen has been proved to have anti-inflammatory, antioxidant, and organ-protective effects. Estrogen has been used as a therapeutic drug in many diseases, such as inflammatory bowel disease [ 14 ], acute spinal cord injury [ 15 ], neurovascular disease [ 16 ], and obesity [ 17 ]. Our previous study found that 17 β -estradiol (E2) suppressed proinflammatory gene expression through promoting the interaction of estrogen receptor (ER) α with NF- κ B p50 and decreasing high glucose-induced interaction of KLF5 with NF- κ B p50 in vascular smooth muscle cells [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a major female hormone, estrogen has been proved to have anti-inflammatory, antioxidant, and organ-protective effects. Estrogen has been used as a therapeutic drug in many diseases, such as inflammatory bowel disease [ 14 ], acute spinal cord injury [ 15 ], neurovascular disease [ 16 ], and obesity [ 17 ]. Our previous study found that 17 β -estradiol (E2) suppressed proinflammatory gene expression through promoting the interaction of estrogen receptor (ER) α with NF- κ B p50 and decreasing high glucose-induced interaction of KLF5 with NF- κ B p50 in vascular smooth muscle cells [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that no significant correlation between BMI and either PPAT HU or SUV was observed in our study, these inconsistent results might be due to the confounding effects of qualitative features of PPAT. Recently, an attempt has been made to pharmacologically modify PPAT features with 5α-reductase inhibitors and estrogen, which is expected to affect the outcomes of prostate cancer [ 49 , 50 ]. Based on the results of the present study, PPAT HU and SUV might be used to select candidates and to monitor treatment response to future therapy that targets PPAT in patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, DES was capable of inhibiting mitochondrial respiration and glycolysis as well as activating ERK in 3T3-L1 adipocytes in an ER-dependent manner [223]. In addition, DES exposure was shown to induce WAT inflammation in obese mice [224].…”
Section: Diethylstilbestrol (Des)mentioning
confidence: 99%